Molecular characterization of protease producing Idiomarina species isolated from Peruvian saline environments - Flores-Fernández C.N. (2019)
All Idiomarina species are isolated from saline environments; microorganisms in such extreme habitats develop metabolic adaptations and can produce compounds such as proteases with an industrial potential. ARDRA and 16S rRNA gene sequencing are established methods for performing phylogenetic analysis and taxonomic identification. However, 16S-23S ITS is more variable than the 16S rRNA gene within a genus, and is therefore, used as a marker to achieve a more precise identification. In this study, ten protease producing Idiomarina strains isolated from the Peruvian salterns were characterized using biochemical and molecular methods to determine their bacterial diversity and industrial potential. In addition, comparison between the length and nucleotide sequences of a 16S-23S ITS region allowed us to assess the inter and intraspecies variability. Based on the 16S rRNA gene, two species of Idiomarina were identified (I. zobellii and I. fontislapidosi). However, biochemical tests revealed that there were differences between the strains of the same species. Moreover, it was found that the ITS contains two tRNA genes, tRNAIle (GAT) and tRNAAla (TGC), which are separated by an ISR of a variable size between strains of I. zobellii. In one strain of I. zobellii (PM21), we found nonconserved nucleotides that were previously not reported in the tRNAAla gene sequences of Idiomarina spp. Thus, based on the biochemical and molecular characteristics, we can conclude that protease producing Idiomarina strains have industrial potential; only two I. zobellii strains (PM48 and PM72) exhibited the same properties. The differences between the other strains could be explained by the presence of subspecies. © 2019, The Korean Society for Microbiology and Biotechnology